2006
DOI: 10.1186/cc4902
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionThe aim of this study was to elucidate the impact of intensive care unit (ICU)-acquired infection on hospital mortality.MethodsPatients with a longer than 48 hour stay in a mixed 10 bed ICU in a tertiary-level teaching hospital were prospectively enrolled between May 2002 and June 2003. Risk factors for hospital mortality were analyzed with a logistic regression model.ResultsOf 335 patients, 80 developed ICU-acquired infection. Among the patients with ICU-acquired infections, hospital mortality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 33 publications
(40 reference statements)
5
29
0
3
Order By: Relevance
“…It is also likely that high rates of ESBL among E.Coli species and high rates of extreme drug resistance among P. aeruginosa and A. baumanii (especially respiratory infections) led to lower percentage of patients being covered appropriately by the initial choice of antibiotic. In this study, the overall mortality rate of ICU acquired infections was 31% and it was comparable to previous studies conducted in other parts of the world where mortality ranged from 10-53.6% (Ylipalosaari et al, 2006;Goldman and Pier, 1993).…”
Section: Discussionsupporting
confidence: 88%
“…It is also likely that high rates of ESBL among E.Coli species and high rates of extreme drug resistance among P. aeruginosa and A. baumanii (especially respiratory infections) led to lower percentage of patients being covered appropriately by the initial choice of antibiotic. In this study, the overall mortality rate of ICU acquired infections was 31% and it was comparable to previous studies conducted in other parts of the world where mortality ranged from 10-53.6% (Ylipalosaari et al, 2006;Goldman and Pier, 1993).…”
Section: Discussionsupporting
confidence: 88%
“…[6][7][8] Em tais unidades os pacientes colonizados e/ou infectados representam a principal fonte de patógenos pois, na colonização apesar de não haver sintomas clíni-cos e imunológicos de infecção, os microrganismos estão presentes nas superfícies cutâneas e mucosas do hospedeiro.…”
Section: 2unclassified
“…[3][4][5] Nas UTIs as taxas de infecções são estimadas entre 18 e 54%, sendo responsável por 5 a 35% de todas as IRAS e por, aproximadamente, 90% de todos os surtos hospitalares. [6][7][8] Em tais unidades os pacientes colonizados e/ou infectados representam a principal fonte de patógenos pois, na colonização apesar de não haver sintomas clíni-cos e imunológicos de infecção, os microrganismos estão presentes nas superfícies cutâneas e mucosas do hospedeiro. 9 Assim, mecanismos de monitorização do perfil microbiológico dos microrganismos associados às IRAS tornam-se uma indispensável ferramenta para apoiar o uso racional de antimicrobianos e as medidas de controle, considerando que a evolução dos microrganismos resistentes (MR) vem ocorrendo de maneira diferenciada em diversos países.…”
Section: Introductionunclassified
“…Degoricija et al (14) evaluated 314 episodes of sepsis in a medical ICU and reported that poor outcome was associated with higher SOFA scores on day 1 in the ICU. Also, Ylipalosaari et al (15) reported SOFA scores of > 8 on admission among patients who subsequently developed an ICU acquired infection. We thought that monitoring the SOFA scores might be useful in the follow-up of the patients with nosocomial sepsis.…”
Section: Discussionmentioning
confidence: 99%